Detached eddy simulations for high speed axial flow fuel pumps with swept and straight blade impellers. Issue 8 (7th November 2016) - Tao, Ran; Xiao, Ruofu; Wang, Fujun
Abstract : Purpose: High speed axial flow pumps are widely used in aircraft fuel systems. Conventional axial flow pumps often generate radial secondary flows at partial-load conditions which influence the flow structure and form a "saddle-shaped" region in the Q-H curve that can destabilize the operation. Thus, the "saddle-shaped" Q-H region must be eliminated. The paper aims to discuss these issues. Design/methodology/approach: The swept stacking method is often used for radial flow control in turbo-machinery impeller blade design. Hence, this study uses the swept stacking method to design a high speed axial flow pump. The detached eddy simulation method and experiments are used to compare the performance of a swept blade impeller in a high speed axial fuel pump with the original straight blade impeller. Both the pump performance and internal flow characteristics are studied. Findings: The results show separation vortices in the impeller with the straight blade design at partial-load conditions that are driven by the rotating centrifugal force to gather near the shroud. The swept geometry provides an extra force which is opposite to the rotating centrifugal force that creates a new radial equilibrium which turns the flow back towards the middle of the blade which eliminates the vortices and the "saddle-shaped" Q-H region. The swept blade impeller also improves the critical cavitation performance. Analysis of the pressure pulsations shows that the swept blade design does not affect the stability. Originality/value: This study is the initial application of swept blades for axial flow liquid pumps. The results show how the swept stacking changes the radial equilibrium of the high density, high viscosity flow and the effects on the mass transfer and pressure pulsations. The swept blade effectively improves the operating stability of high speed fuel pumps.